PERANCANGAN DAN PEMBUATAN GAME EDUKASI RIGHT THINKING DENGAN MENTODE GREEDY - Azrai Sirait (Universitas Asahan, 2017)
Abstrack - Right thinking education game is a software application that can be used as a learning media like other educational game applications. This educational game application can be installed using the Windows operating system. For computer users who like learning activities with educational games on a computer, it is strongly recommended to use this application even though this educational game application is still far from perfect with good software such as animation based educational games with macromedia flash and so on. The right thinking education game is unique compared to other educational games. This educational game has a special design in the system that can be updated on the contents of the practice questions. In this process it can be done by the users themselves without having to update via the internet or the payment process but it can be done very easily so the user is not bothered and the user can be more comfortable playing the right thinking game. Keywords - Games, Education, Greedy, Analysis, Learning.